The circular economy and sustainable development in the European Union's new member states - Mihaela Simionescu (Economics, Management and Sustainability)
The transition to a circular economy could not be avoided, but it should be oriented to ensure the achievement of sustainable development. The limited data availability and lack of enough studies for new EU member states are the main gaps in the literature partially covered by this research. A macroeconomic approach based on panel data models and Bayesian random linear regression models was conducted for Cyprus, Latvia, Lithuania, Hungary, Poland, Romania, Slovenia, and Slovakia from 2008-2020. The results indicated that gross investment in tangible goods and more employed people in circular economy sectors are necessary to support economic growth. Moreover, mapping the jobs in a circular economy is required to support a sustainable circular economy.